Optic neuritis following COVID-19 vaccination: Do autoimmune diseases play a role? - Pirani, Vittorio; Pelliccioni, Paolo; Carpenè, Maria Jolanda; Nicolai, Michele; Barbotti, Federica; Franceschi, Alessandro; Mariotti, Cesare (European journal of ophthalmology, 2023)
We report two cases of optic neuritis following Pfizer-BioNTech COVID-19 vaccination in patients with autoimmune diseases. Post-vaccine optic neuritis, although rare, is reported in the literature and an autoimmune mechanism seems to be involved, especially in genetically predisposed subjects. Report of two cases of optic neuritis following COVID-19 vaccination in patients with autoimmune diseases. He novelty of this article is the fact that the two patients had a medical history of autoimmune diseases (Hashimoto thyroiditis and ankylosing spondylitis), a point of interest for research because it is not yet clear whether this could constitute a risk factor for adverse events after vaccination. The reactogenicity of COVID-19 mRNA vaccine in individuals suffering from immune-mediated diseases is yet to be elucidated and it is being increasingly investigated. Our paper supports the hypothesis that patients who are already affected or predisposed to autoimmune or autoinflammatory disorders should be carefully evaluated for the benefits and risks of COVID-19 mRNA vaccination.